2012
DOI: 10.1007/s13365-012-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human herpesvirus U94/REP antibodies and DNA in Tunisian multiple sclerosis patients

Abstract: Human herpesvirus 6 (HHV-6) has been linked to the pathogenesis of multiple sclerosis (MS). Based on antibody detection and quantitative HHV-6 polymerase chain reaction assay, this study aimed to analyze the possible association between infection with HHV-6 and MS. A total of 131 serum samples were analyzed by ELISA for the presence of specific antibodies to HHV-6 latency-associated U94/REP protein: 68 serum samples from 60 MS patients (20 in relapse and 48 in remission phase) and 63 serum samples from 63 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…A 2013 study examined antibodies to a latency-promoting protein, U94/REP, and found elevated IgG levels in Tunisian MS patients compared to controls; for eight patients with samples collected during relapsing and remitting phases, significantly higher titers were detected during the relapsing phases [31]. The finding of an elevated U94 IgG response in MS patients versus controls agrees with previous findings in an Italian cohort [32], and adds the observation of higher titers during relapse versus remission.…”
Section: Traces Of Hhv-6 In the Periphery: Virus Detection And Virus-mentioning
confidence: 99%
“…A 2013 study examined antibodies to a latency-promoting protein, U94/REP, and found elevated IgG levels in Tunisian MS patients compared to controls; for eight patients with samples collected during relapsing and remitting phases, significantly higher titers were detected during the relapsing phases [31]. The finding of an elevated U94 IgG response in MS patients versus controls agrees with previous findings in an Italian cohort [32], and adds the observation of higher titers during relapse versus remission.…”
Section: Traces Of Hhv-6 In the Periphery: Virus Detection And Virus-mentioning
confidence: 99%
“…YKL-40 has been proposed as a biomarker of multiple sclerosis [90]. CSF level of YKL-40 is increased in MS [91] and is a prognostic marker in MS [92]. Enhanced skin expression of IFIH1 (MDA5) in dermatomyositis and related autoimmune diseases [93].…”
Section: Discussionmentioning
confidence: 99%
“…Fredj et al [38] reported HHV-6 DNA in peripheral blood samples from 6.1% of patients with RRMS in remission and in 2.0% of healthy controls and Sotelo et al [36] in PBMCs from 2% of patients with RRMS in remission and in none of the healthy controls. Ben-Fredj et al [42] reported HHV-6 DNA in whole blood from 6.7% of patients with MS from Tunisia and in 3.2% of healthy controls and Hon et al [37] in 3.2% of patients with MS from South Africa and absent in healthy controls. Ablashi et al [41] reported higher prevalence rates; the authors reported viral DNA in PBMCs from 66.7% of patients with MS in remission, but also in 60.0% of healthy controls, and therefore equally higher for both patients and controls.…”
Section: Authorsmentioning
confidence: 98%